E-cadherin/CD34 double immunostaining in placental diagnosis - Jerzy Stanek (Polish Journal of Pathology)
Placental foetal vascular malperfusion (FVM) may be responsible for complicated foetal or neonatal condition. By highlighting endothelial fragmentation, the double E-cadherin/CD34 immunostain highlights distal villous endothelial fragmentation of recent FVM not seen on haematoxylin-eosin stained sections. We routinely perform the stain on a grossly unremarkable placental sections of placentas predominantly from pregnancies with mass-forming foetal anomalies and umbilical cord complications. The stain can upgrade the FVM and/or reveal its temporal heterogeneity, both useful in establishing the cause of foetal death or poor neonatal condition. It also highlights the basement membranes of syncytiotrophoblastic cells which, in conjunction with endothelial staining, is helpful in the diagnosis of widening thereof in distal villous hypomaturity. It can distinguish mineralised stem occluding thrombi from mineralised trophoblastic pseudo inclusions – the former outlined by CD34, the latter by E-cadherin – thus helping to differentiate FVM from placental aneuploidies. The E-cadherin component helps in the diagnosis of trophoblastic lesions of shallow placental implantation featuring an increased number of extravillous trophoblasts in placental membranes and chorionic disc. Therefore, the double immunostain is helpful in histological diagnosis of placental lesions and patterns of injury.